A lysosome targetable fluorescent probe for endogenous imaging of hydrogen peroxide in living cells. Issue 26 (15th March 2017) - Reja, Shahi Imam; Gupta, Muskan; Gupta, Neha; Bhalla, Vandana; Ohri, Puja; Kaur, Gurcharan; Kumar, Manoj
Abstract : A lysosome targetable naphthalimide based fluorescent probe has been designed and synthesized for selective imaging of H2 O2 in different cells, tissues and in vivo models. Abstract : A lysosome targetable naphthalimide based fluorescent probe (LyNC) has been designed and synthesized which detects hydrogen peroxide (H2 O2 ) with high selectivity and sensitivity in brain tissues and in living nematodes among various ROS/RNS tested. Further, the probeLyNC was successfully employed in exogenous and endogenous imaging of H2 O2 in living cell lines.